A atuação da comissão de valores mobiliários enquanto órgão regulador do mercado de capitais: uma análise à luz do atual contexto político-econômico brasileiro - Liberalino, Ana Paula da Silva (Universidade Federal Rural do Semi-Árido, 2018)
The securities market – or capital market – is the segment of the financial system in which the purchase and sell of securities, such as stocks, bonds, subscription bonus, and others are executed. Its objective is to enable the direct transfer of resources between economic agents: investors and companies (publicly held companies). So, on the one side, there is the companies’ interest in obtaining financing for their activities and projects, and, on the other side, there are legal or individual people who have surplus financial resources and, so, invest in some business activity seeking the increase of their own wealth. That dynamic is of great importance for enterprise development and, consequently, for the country’s economic growth. Recognizing this fact, Brazilian law assigns to the Brazilian Securities and Exchange Commission (CVM) the finality of regulating and supervising the capital market, as well as to sanction an economic agent when find out the occurrence of an illicit against that segment of the financial system. An efficient performance of CVM generate confidence to investors, stimulating the increase in the securities’ purchase and sell. However, the current Brazilian political and economic context, affected by the numerous scandals related to the involvement of large companies in corruption’s acts, has substantially damaged the CVM’s credibility and, consequently, the capital market. The problem is intrinsically related to the effectiveness of its functions of supervising and sanctioning, in view of the slowness in its processes - when nonexistent - of investigating and sanctioning the financial illicit, in contrast to the agility demanded by the market – especially in view of the current conjuncture e of crisis. In view of these notes, this paper aims to: (i) explain about the capital market and its importance to business activity; (ii) analyze the CVM's functions and the effects of its performance in light of the current political and economic context; and (iii) discuss the Provisional Presidential Decree n.º 784/2017 and to propose other solutions related to the CVM's activities as a regulator of the Brazilian capital market.
Monografia
Keywords: Comissão de valores mobiliários; Mercado de capitais; Regulação; Brazilian securities and exchange commission; Capital market; Regulation; CIENCIAS SOCIAIS APLICADAS::DIREITO